Moderasi Pemikiran Fikih Hubungan Antarumat Beragama di Majelis Tarjih dan Tajdid Muhammadiyah - Fanani, Ahwan (IAIN Surakarta, 2017)
Muhammadiyah is credited as moderate islamic organization due to its long and familiar encounter with national and social issues in Indonesia. The question on how Muhammadiyah position on the issues of religious relationship and on how Muhammadiyah formulates its view on the issue lead to the question on religious opinion produced by official body of Muhammadiyah that is in charge to give answer. The formulation of Muhammadiyahâs stance related to the relationship between moslems and nonmoslems is under authority of Majelis Tarjih and Tajdid (MTT), formal board in Muhammadiyah issuing fatwas or religious opinions related to religious and social problems faced by Muhammadiyahâs members. From this boardâs decisions, the official stance of Muhammadiyah can be analyzed using the spectacle of moderatism. Muhammadyah has two different stances in dealing with religious issues. It has clear and relatively strict position on akida (belief) and ibada (ritual) but it has loose and open position in muamala (daily relationship) to other people. However, Muhammadiyah develops broader approach in understanding Islamic text and accepting more diverse legal sources, such as sadd dzariah and maslahah. In sum, the stance of Muhammadiyah to the relationship between moslems with other religious people will be influenced by the division between akida-ibada and muamalah aspects, which it will be more flexible to the later. This divison enables it to develop more moderat view or legal opinion related to the relationship between moslems and other religious people.Â